1999
DOI: 10.4141/s98-049
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and mineral-associated organic matter in water-stable aggregates as affected by mineral fertilizer and manure applications

Abstract: Aoyama, M., Angers, D. A. and N'Dayegamiye, A. 1999. Particulate and mineral-associated organic matter in water-stable aggregates as affected by mineral fertilizer and manure applications. Can. J. Soil Sci. 79: 295-302. Application of cattle manure generally improves soil structure and organic matter (OM) content. However, changes in forms and location of OM within the aggregate structure are less well known. The effects of long-term (18-yr) applications of cattle manure (20 Mg ha -1 yr -1 ) and NPK fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(101 citation statements)
references
References 32 publications
13
85
2
1
Order By: Relevance
“…Thus, manure application led to the preferential accumulation of protected C and N in the macroaggregates. This physical protection could help to explain the preferential accumulation of OM in the small macroaggregates induced by the manure application as observed by Aoyama et al (1999). The effect of NPK fertilization on the amount of macroaggregate-protected N is also noteworthy and suggests that fertilizer-derived N can accumulate in a relatively labile form, which is also physically protected within the macroaggregates.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, manure application led to the preferential accumulation of protected C and N in the macroaggregates. This physical protection could help to explain the preferential accumulation of OM in the small macroaggregates induced by the manure application as observed by Aoyama et al (1999). The effect of NPK fertilization on the amount of macroaggregate-protected N is also noteworthy and suggests that fertilizer-derived N can accumulate in a relatively labile form, which is also physically protected within the macroaggregates.…”
Section: Resultsmentioning
confidence: 89%
“…Every 5 yr, lime was applied on all plots at about 3 Mg ha -1 , based on soil analysis. Further details of the trial have been reported by N'Dayegamiye (1996) and Aoyama et al (1999).…”
Section: Site Description and Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil total C and N were determined for all five depths by dry combustion on soil ground and sieved at 0.5 mm. The POM was determined for all five depths using a modification of the method outlined in Aoyama et al (1999). Briefly, 25 g of air-dry soil (2 mm) was mixed with distilled water (100 mL) and 10 glass beads (5-mm diameter).…”
Section: Crop and Soil Sampling And Analysismentioning
confidence: 99%
“…Long-term studies with organic amendments have also demonstrated the benefits to soil physical properties for both soil physical form and stability (Christensen and Johnston 1997;Haynes and Naidu 1998;Blair et al 2006). These benefits, from manure addition in particular, are often attributed to the enhancement of soil organic matter content (Aoyama et al 1999;Assefa et al 2004;Blair et al 2006). The extent and degree of change in soil properties are dependent on rate of manure application and the number of years of application (Miller et al 2002;Hao et al 2003).…”
mentioning
confidence: 99%